ANALISIS KESTABILAN LERENG UNTUK MENENTUKAN GEOMETRI LERENG PADA AREA PENAMBANGAN PIT MUARA TIGA BESAR SELATAN PT.BUKIT ASAM (PERSERO) TBK, TANJUNG ENIM, SUMATERA SELATAN - Azhary Rahim; Bambang Heriyadi; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2015)
One of few factors that should watch over in open pit mining is geotechnical on rocks lithology in mining area. Since designing of slope geometry there are many factors so thus factors must be input as a parameter to determine slope stability.The type of dominant failures occur in Muara Tiga Besar Area are wedge and planar sliding which caused by discontinuity and sheer slope orientation. This research used stereographic method to determine type and aim of failure based on discontinuity and slope orientation. Stereographic analyses result will conduct and optimal slope angle. Furthermore modeling simulation will be done for single and overall slope to determine its geometry and factor of safety based on geotechnical data such as cohesion and friction angle for each materials.Based on stereographic analysis to overburden A1 single slope angle are conducted 41o , 40o, 42o, 39o, and for lower C is conducted 41o, 42o, 41o, and 42o. in order to get an optimal single slope then it must be conducted from simulation and the result for overburden A1 is 47o as optimal slope angle with factor of safety amount of 1.302 for saturated condition and dry condition 1.727 and for lower C the result of optimal slope angle is 43o, whose factor of safety is 1.305 for saturated condition and 1.886 for dry condition. Afterwards modeling simulation is been done to overall slope in A-A’ and B-B’ section. Factor of safety in highwall area is 1.323 with 27.4o overall slope angle and 155 meters high. In other hands, factor of safety in lowwall area is 1.318 with 25.2o overall slope angle and 192 meters high.